Evolocumab - CDA-AMC (Canadian Journal of Health Technologies, 2026)
The Formulary Management Expert Committee (FMEC) recommends that evolocumab be reimbursed for the treatment of adult and pediatric patients aged 10 years and older with homozygous familial hypercholesterolemia (HoFH) who require additional lowering of low-density lipoprotein cholesterol (LDL-C), provided certain conditions are met. Evolocumab may be initiated for the treatment of adult and pediatric patients aged 10 years and older with HoFH who require additional lowering of LDL-C. Evolocumab may be renewed if all of the following conditions are met: an assessment of response at 12 weeks after initiation and a clinically relevant reduction in LDL-C. Initiation of evolocumab should be limited to clinicians with expertise in the diagnosis and management of dyslipidemia. Evolocumab should be priced no higher than the least costly comparator for this population.